Actions anchored by concepts: defective action comprehension in semantic dementia. Issue 12 (4th August 2006) - Nishio, Y; Kazui, H; Hashimoto, M; Shimizu, K; Onouchi, K; Mochio, S; Suzuki, K; Mori, E
Abstract : Objective: To study the ability of patients with semantic dementia to understand actions, in order to examine the contribution of semantic memory to action comprehension. Methods: The ability to comprehend symbolic and instrumental actions was assessed in 6 patients with semantic dementia and 10 healthy controls. The patients were also given the imitation test of meaningful and meaningless actions. Results: In all patients with semantic dementia, comprehension of both symbolic and instrumental actions was defective. The comprehension of symbolic actions was more impaired than that of instrumental actions. Their ability to imitate other's actions was well preserved. Conclusion: This study showed that comprehension of action was impaired in semantic dementia, suggesting that semantic memory has an important role in comprehension of human action.